Comparison of the preventive effects of Murraya exotica and Murraya paniculata on alcohol-induced gastric lesions by pharmacodynamics and metabolomics. (5th December 2021) - Lu, Mengqiu; Du, Zhiyong; Yuan, Shuo; Ma, Qing; Han, Zhenzhou; Tu, Pengfei; Jiang, Yong
Abstract: Ethnopharmacological relevance: Multi-source phenomenon is very common for traditional Chinese medicine (TCM). Both Murraya exotica L. (ME) and Murraya paniculata (L.) Jack (MP) are used as the source plants of Murrayae Folium et Cacumen (MFC), a traditional Chinese medicine recorded in Chinese Pharmacopoeia for promoting qi and relieving pain, mainly for the treatment of stomach pain, rheumatism and arthralgia. However, up to now, there has been no comparative study of these two plants on their efficacies and mechanisms, thus, further research is needed to evaluate their similarity and difference in order to judge the reasonability for their common usage. Aim of the study : This study aims to compare the effects and potential mechanisms of ME and MP, the two source plants of MFC on gastric lesions in rats by pharmacodynamics and metabolomics. Materials and methods: A rat model of gastric lesions induced by 70% aqueous ethanol and 150 mmol/L HCl was established and adopted to evaluate the gastric protective effects of ME and MP by analysis of the lesion index, histopathological changes (observed by H&E staining and TUNEL staining) and cytokine levels (IL-1β, IL-6, TNF-α, MTL, and GAS). The potential mechanisms were investigated by LC-MS metabolomic analysis of the rat plasma. Results: ME and MP showed the similar effects on improving the lesions of rat stomachs and reducing the cytokine levels related to inflammation and digestion of rats. The metabolomics results showed that the metabolism of rats with gastric lesions was abnormal mainly in lipid metabolism, energy metabolism, and amino acid metabolism. ME and MP demonstrated a similar metabolic modulation for gastric lesions by acting on the similar pathways and metabolites. Also, PLA2 pathway was proved as an important pathway for ME and MP modulation of glycerophospholipid metabolism in gastric lesions. Conclusions: Our results proved that it is feasible and reasonable to use both of ME and MP as the source plants of MFC, at least for the treatment of gastric lesions, due to their similar pharmacodynamics and metabolic modulation ability. Moreover, the combination of pharmacodynamics and metabolomics is an efficient means for multi-source TCM study. Graphical abstract: Image 1 Highlights: Comparison of Murraya exotica (ME) and Murraya paniculata (MP) by pharmacodynamics and metabolomics. ME and MP showed the similar effects on improving gastric lesions. ME and MP demonstrated a similar metabolic modulation for gastric lesions. It is reasonable to use ME and MP as the source plants of Murrayae Folium et Cacumen. Combining pharmacodynamics and metabolomics is efficient for multi-source TCM study.